2014
DOI: 10.1073/pnas.1323405111
|View full text |Cite
|
Sign up to set email alerts
|

CD1d-unrestricted NKT cells are endowed with a hybrid function far superior than that of iNKT cells

Abstract: Significance The Immunological Genome Project Consortium has recently identified a gene-expression program that links invariant natural killer T (iNKT) cells to NK cells. While this is true, our study provides molecular and functional evidence demonstrating that CD1d-independent NKT cells are uniquely programmed with a hybrid function far superior to that of iNKT cells. Such a unique feature enables this subset of NKT cells to contribute to adaptive immunity (like T cells) and at the same time act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 47 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…Both Nkp46 and Gzmb were very modestly expressed in the wild-type thymic and splenic iNKT cells at steady state (Fig. 6), similar to what has been recently reported (43). Removal of Bcl11b resulted in the up-regulation of Nkp46 and Gzmb in all of the three effector subsets both in thymus and spleen (Fig.…”
Section: Bcl11b Restricts Expression Of Inkt17 Program In Inkt1 and Isupporting
confidence: 84%
“…Both Nkp46 and Gzmb were very modestly expressed in the wild-type thymic and splenic iNKT cells at steady state (Fig. 6), similar to what has been recently reported (43). Removal of Bcl11b resulted in the up-regulation of Nkp46 and Gzmb in all of the three effector subsets both in thymus and spleen (Fig.…”
Section: Bcl11b Restricts Expression Of Inkt17 Program In Inkt1 and Isupporting
confidence: 84%
“…Interestingly, a recent study reported that vectors expressing the NKG2D ligand RAE-1γ dramatically enhanced the effectiveness of CD8 + T-cell response suggesting a promising approach in the development of CD8 + T-cell–based vaccines (41). Accordingly, one possible candidate for the origin of innate CD8 + NKT cell function is the subset of MHC-unrestricted NKT cells (42, 43). These NKT cells have been recently described as sharing many characteristics of NK cells including the expression of the killer cell lectin-like receptors (Klr), the rapid production of IFNγ in response to cytokine stimuli (IL-12/IL-18), and the potent cytotoxic program (granzyme B) in response to innate signals (Poly:IC) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, one possible candidate for the origin of innate CD8 + NKT cell function is the subset of MHC-unrestricted NKT cells (42, 43). These NKT cells have been recently described as sharing many characteristics of NK cells including the expression of the killer cell lectin-like receptors (Klr), the rapid production of IFNγ in response to cytokine stimuli (IL-12/IL-18), and the potent cytotoxic program (granzyme B) in response to innate signals (Poly:IC) (43). Notably, the identity of these T cells as MHC-unrestricted T cells makes them excellent candidates to serve as professional innate T cells while maintaining adaptive functions.…”
Section: Discussionmentioning
confidence: 99%
“…They constitute a subset of T lymphocytes that express some natural killer cell receptors. However, they are not restricted by CD1d molecules, so they are also called CD1d independent NKT (CD1d ind NKT) [ 35 ]. Scientists have confirmed a highly specialised effector-memory phenotype of these lymphocytes, thus their percentage in peripheral blood increases with age.…”
Section: Subsets Of Natural Killer T-cellsmentioning
confidence: 99%